Lily and the prisoner of magic - Webb, Holly (London : Orchard, 2012)
Sisters Lily and Georgie voyage far from home looking for help to rescue their father, who has been imprisoned for being a magician, and find a magician named Rose.
5.2
3-6.
3-6
Keywords: Magic -- Juvenile fiction; Magicians -- Juvenile fiction; Sisters -- Juvenile fiction; Fantasy; Magic -- Fiction; Magicians -- Fiction; Sisters -- Fiction; Magic -- Fiction; Magicians -- Fiction; Sisters -- Fiction; Fantastic fiction; Fantastic fiction